Special hearing to control the use of the liquidation of alimony accrued in the civil process (SCIÉNDO INGENIUM, 2021)
The objective of this research is to establish a mechanism that allows control of the expenditure of alimony accrued to guarantee the right to food that adolescent children in our country have. The inductive method was used, since the present investigation aims to determine a solution for the benefit of minors; the analytical method, by which the regulations of our legal system and comparative law were analyzed. With the analyzed work, it was determined that there are no parameters to control the use of accrued alimony; which causes the rights of children and adolescents to be violated, such as having the right to a dignified life. There is no regulation in our country that constitutes an important tool by means of which the effective and efficient use of the liquidation of alimony in the civil process is controlled. In comparative law, as is the case in the countries of Ecuador and Uruguay, there is a regulation that the obligor requires the mother or the legal representative of a minor to account for the use of alimony.
Keywords: special audience; control of use; liquidation of alimony accrued; civil process